Tracking Nitrogen Source Using δ15N Reveals Human and Agricultural Drivers of Seagrass Degradation across the British Isles - Jones, Benjamin L.; Cullen-Unsworth, Leanne C.; Unsworth, Richard K. F. (Frontiers in Plant Science, 2018)
Excess nutrients shift the ecological balance of coastal ecosystems, and this eutrophication is an increasing problem across the globe. Nutrient levels may be routinely measured, but monitoring rarely attempts to determine the source of these nutrients, even though bio-indicators are available. Nitrogen stable isotope analysis in biota is one such bio-indicator, but across the British Isles, this is rarely used. In this study, we provide the first quantitative evidence of the anthropogenic drivers of reduced water quality surrounding seagrass meadows throughout the British Isles using the stable nitrogen isotope δ15N. The values of δ15N ranged from 3.15 ‰ to 20.16 ‰ (Mean  SD = 8.69  3.50‰), and were high within the Thames Basin suggesting a significant influx of urban sewage and livestock effluent into the system. Our study provides a rapid ‘snapshot’ indicating that many seagrass meadows in the British Isles are under anthropogenic stress given the widespread inefficiencies of current sewage treatment and farming practices. Ten of the eleven seagrass meadows sampled are within European marine protected sites. The ten sites all contained seagrass contaminated by nutrients of a human and livestock waste origin leading us to question whether generic blanket protection is working for seagrasses in the UK. Infrastructure changes will be required if we are to develop strategic wastewater management plans that are effective in the long-term at protecting our designated Special Areas of Conservation. Currently, sewage pollution is a concealed issue; little information exists and is not readily accessible to members of the public.